Valorisasi Limbah Batang Kayu Manis Menjadi Sumber Energi Alternatif Bersih Melalui Sistem Pirolisis Drum Tertutup di Nagari Malalak Timur: Empowerment of Farmers through the Utilization of Cinnamon Wood Waste as an Alternative Energy Source Using Closed-Drum Pyrolysis in Nagari Malalak, Agam Regency - Darwison Darwison; Zaini Zaini; Silvia Permata Sari; Deddi Prima Putra; Firman Ridwan; Fauzan Wafi; Annita Elfia Rosa; Afwan Nasution; Ghina Salsabila (LPPM Universitas Andalas, 2026)
Nagari Malalak Timur is a major cinnamon (Cinnamomum burmannii) production center, but faces critical post-harvest challenges. Weather-dependent drying processes delay sales, while abundant stem and leaf waste are openly burned, causing severe air pollution and energy loss. This community empowerment program explicitly aims to solve these environmental and economic issues by converting cinnamon stem waste into clean alternative energy using an optimized closed-drum pyrolysis system, while simultaneously enhancing farmers' technical capacities. The participatory action research approach involved the Toboh Organik Farmers Group. Implementation stages included waste potential mapping, fabricating a 30-kg-capacity pyrolyzer equipped with a Raspberry Pi Pico microcontroller and an electric blower for precise thermal control, and conducting comprehensive operational, maintenance, and safety (K3) training. Charcoal quality was evaluated against the SNI 01-6235-2000 standard. The intervention yielded significant improvements. Technologically, the pyrolyzer achieved a high conversion efficiency of 38%, producing premium charcoal with a calorific value of 6,780 kcal/kg and 6.2% moisture content. Environmentally, the integrated re-burning system reduced hazardous smoke emissions by 60% compared to open burning. Socio-economically, the program successfully decreased agricultural waste by over 60% and increased farmers' overall income by 30–35% through the creation of a new marketable product. These findings confirm that the introduction of controlled, locally adapted pyrolysis technology not only resolves waste and weather-dependency problems but also fosters rural energy self-sufficiency. The establishment of the